Trends and patterns in the global burden of intracerebral hemorrhage: a comprehensive analysis from 1990 to 2019 - Sun, Tong; Yuan, Yikai; Wu, Ke; Zhou, Yicheng; You, Chao; Guan, Junwen (Frontiers in Neurology, 2023)
Objective Intracerebral hemorrhage (ICH) is a significant cause of global mortality and morbidity. This study aimed to analyze the burden of ICH and its variation trends across 204 countries and territories from 1990 to 2019. Materials and methods The study population comprised individuals of all ages and genders with ICH in 204 countries and regions between 1990 and 2019. Utilizing data from the Global Burden of Disease (GBD) study 2019, we collected information on age-standardized incidence rate (ASIR), age-standardized death rate (ASDR), and disability-adjusted life-years (DALYs) rate, which were compared by age, gender, and socio-demographic index (SDI). Results In 2019, there were an estimated 3.4 million (3.0–3.9) incident cases, resulting in 2.8 million (2.6–3.0) deaths and 68.5 million (63.2–73.6) DALYs due to ICH. Between 1990 and 2019, the absolute number of incident cases, deaths, and DALYs increased by 43.0% (41.0–45.0), 37.0% (22.0–51.0), and 25.0% (12.0–36.0), respectively. However, the ASIR, ASDR, and DALYs showed a decreasing trend of-29.0% (−28.0 to −30.0), −36.0% (−29.0 to −43.0), and − 37.0% (−43.0 to −31.0), respectively. Countries with lower SDI tended to have higher ASIR, ASDR, and DALY rates. Conclusion While the ASDR and DALY rates decreased from 1990 to 2019, the decline in ASIR was less pronounced. The global burden of ICH remains high, exhibiting significant variation across different genders, age groups, and SDI levels.